Physiologic parameters and their response to handling stress in a neotropical migratory shorebird during the nonbreeding season - D'amico, Veronica Laura (2017)
Physiologic traits are promising indicators of population health in the face of rapidly changing environments. We obtained values of diverse physiologic parameters for Two-banded Plovers (Charadrius falklandicus) in coastal sites in Patagonia, Argentina, with the objectives of determining the timeline in which these parameters become affected by the stress of capture and handling and of obtaining reference values for future monitoring of these populations. We analyzed packed cell volume, white blood cell profile, heterophil/lymphocyte ratio, bacterial agglutination titer, and total protein, glucose, triglyceride, and cholesterol levels in apparently healthy birds. Glucose, total white blood cell count, lymphocytes, and eosinophil levels showed changes with handling times >60 min after capture. The remaining parameters did not manifest significant alterations in response to capture and handling of up to 232 min (average¼105.2, SD¼56.7). Therefore, although researchers should attempt to obtain blood samples as soon as possible after capture, inclusion of physiologic parameters in monitoring studies of species not easily sampled in a few minutes, such as Two-banded Plovers and other shorebird species during migration, should not be discouraged. Here we provide a physiologic report for the species that can be considered as reference values during the nonbreeding season at Patagonian coastal sites.